The Optimasi Jaringan 4G LTE Menggunakan Metode Coverage Planning dengan Frekuensi 1800 MHz di Kecamatan Cibitung - Ni Ketut H.D; Fauzia Haz; Reza Zanarsyah Putra (EPSILON: Journal of Electrical Engineering and Information Technology, 2025)
As a region with rapid urbanization and residential development, Cibitung District faces challenges in achieving equitable 4G network quality. Optimization of 4G coverage has become an essential need. Therefore, this study focuses on optimizing the 4G LTE network in Cibitung District using the coverage planning method through link budget calculations to obtain the Maximum Allowable Path Loss (MAPL). Two propagation models, Okumura-Hata and Cost-231, were then used to estimate the coverage area per cell and the required number of sites. The optimization simulation was conducted using Atoll software to analyze signal coverage distribution based on the Reference Signal Received Power (RSRP) parameter. This method was chosen to estimate coverage capable of reducing blank spots and reaching the entire study area. The results show that using the Okumura-Hata model requires 16 BTS sites, while the Cost-231 model requires 21 BTS sites to cover the entire region. Based on RSRP, good-quality coverage (RSRP ≥ -100 dBm) using the Okumura-Hata model reaches 35.120 km² or 97.95%, while the Cost-231 model only covers 14.921 km² or 41.5% of the total area. This proves that appropriate propagation model selection and coverage optimization strongly influence 4G network implementation in urban areas.